The effects of past soil and crop management on some physico-chemical properties of an acid sulphate soil - Makalew, Afra Donatha Nimia; Upasena, S.H; Apisit Eiumnoh; Murali, N.S; Eastern Indonesia Universities Development Project (EIUDP) - CIDA (Bangkok : Asian Institute of Technology, 1993)
This study was conducted in Agricultural and Food Engineering Farm of the Asian Institute of Technology Bangkok, during dry season of 1993. The objective of this investigation was to document the effects of soil and crop management on some physico - chemical properties of an acid sulphate soil in order to evaluate their changes in accordance with the cropping systems that were practiced over the last 7 years. The soil samples were taken from the four different plots which have had different types of farming history since 1986. An indicator crop, maize (Zea mays.L) was grown in those four plots to support the data of soil laboratory analysis. Generally, the different cropping systems practiced in each plot over the last 7 years have contributed to soil chemical and physical characteristics. It was observed that there were positive changes to some soil properties in each plot due to different farming practices in the respective plots. The data derived from the soil analysis was well supported by the data gathered through the indicator crop to the effect that the different types of farming activities carried out during the last seven years hctve had changed certain physico - chemical properties of the soil under this investigation. For e.g., Liming has decre(,lsed the total acidity' exchangeable aluminum, hydrogen and has increased the excharigeable c~lcium which have resulted in improving the condition for better plant growth.
Thesis (M.Sc.) - Asian Institute of Technology, 1993
A thesis submitted in partial fulfilment of the requirement for the degree of Master of Science.
Keywords: Acid sulphate soils